Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Kantor Sekertariat Daerah Kabupaten Aceh Barat - Rusma Setiyana; Lasmidar (Jurnal Ilmu Ekonomi, 2022)
This study aims to identify whether the workload affects the performance of employees at the West Aceh Regional Secretariat office, and whether the work environment affects the performance of the employees of the West Aceh Regional Secretariat Office. The samples involved in this study were as many as 20% 0f population. This study used a quantitative approach and a questionnaire as the instrument in the data collection technique. SPSS version 25.0 was employed to analyze the data obtained. The results of the study stated that based on the results of the T test, workload had a positive effect on employee performance and the work environment also had an effect on employee performance. Similar to the T test, the results of the F test also show that the two variables (workload and work environment) affected employee performance. Furthermore, the results of the coefficient of determination test show that 39.50% of employee performance was influenced by workload and work environment.